Developing a green nursing workforce to mitigate healthcare emissions and improve human health - Mills, Anne (Evidence-based nursing, 2024)
BMC Nursing 2024;23:229.1 Implications for practice and research Healthcare emissions contribute to climate change and threaten human health; therefore, nurses have a professional obligation to become environmentally informed, take action to reduce healthcare emissions and support green solutions. Green health teams and systems provide opportunities for education and collaborative work to identify and establish low-carbon equipment alternatives, consider energy efficiency, minimise waste, decrease pharmaceutical pollution, appraise water use, improve transport systems, review hospital food menus to reduce waste and improve health, and develop solutions for environmental challenges relevant to work settings.5 Organisations such as the National Health Service (NHS) in the UK have harnessed the power and reach of green teams by introducing competitions between teams to facilitate change and gain extra publicity and support for their health improving environmental work.6 In addition, collaborative working and networking within and between team members has the potential for more ambitious projects and goals. Nurses can also be greener in their own personal lives, making decisions about car journeys versus public transport, recycling actions and food choices, all of which have an impact on personal and collective carbon footprints.